Using the ¨writing for learning¨ approach to reinforce writing in english in fifth graders at glenn doman school¨ (2016)
The world is moving constantly and as teachers we must advance as well, using as many technology resources as we can with our learners; that is the real world now, teachers that do not know anything about technology are outdated, if we want to do our best effort to encourage students to learn, we must be in their world not in ours, if a pupil cannot learn the way we teach, for sure we should teach the way they learn. Having in mind how important is technology now, the main role that it plays in the education field, as a teacher, I will apply a project, which pretends to reinforce some of the writing microskills using the ¨writing for learning¨ approach employing some digital resources. The main idea is to help students retain more information, understand concepts more rapidly and be more enthusiastic about what they are learning. I consider it is important to use the proper material to work with students in that way learners practice grammar in meaningful contexts. The initial idea is to reinforce some writing microskills and in that way prepare fifth graders to present the bimonthly Oxford exams which test students mechanics of writing; moreover learners during their whole life will be faced to present those kinds of exams which test all the language skills, and one of the most important is the writing evidenced in all the exam. One example is the Test of English as a Foreign Language or is a standardized test of English language proficiency for non-native English language, TOEFL is one of the two major English-language tests in the world that most students take in order for them to study in a foreign country, to apply for a scholar ship or to test students English language proficiency. We all know how difficult is to engage the children in learning. However they enjoy the process when the teacher uses technology in order to make classes more interactive and interesting, It is not a secret that the involvement technology in the educational process makes education more enjoyable both for the teachers and the learners.